PENGEMBANGAN BRANDING PRODUK DAN STRATEGI DIGITAL MARKETING PADA UMKM BALINESE PROJECT - Narayana, I Wayan Gede; Ayu Saraswati Winarta, Kadek; Rai Masita Dewi, Ni Made; Agung Ngurah Bajra Dipa Narotama, Anak; Samsudin, Mamuhamad (STKIP PGRI SITUBONDO, 2024)
partner understanding regarding product branding; 2) not yet optimal in determining digital marketing strategies and digital technology in marketing efforts; 3) partners are not yet optimal in recording and managing trade product inventories. The target participants in this PKM are 2 people. The implementation method for the Community Partnership Program (PKM) is divided into several stages, namely; planning, implementation, evaluation, and reflection. The results of the service activities showed that (1) before the training activity the partners' understanding was lacking in product branding, but after the training all participants understood the concept of product branding through developing product packaging designs in good categories; (2) before the training activity, partners' understanding was lacking in implementing marketing strategies and digital marketing, but after the training all participants understood how to use digital marketing strategies, namely Google My Business and E-commerce (Tokopedia) in the good category; (3) Before the activity, partners lacked understanding in managing stock, but after the training all participants understood how to manage stock with the help of the Inventory Management application. In this activity, all participants gave positive responses